2018
DOI: 10.1007/s12369-018-0475-6
|View full text |Cite
|
Sign up to set email alerts
|

Design and Impact of a Teacher Training Course, and Attitude Change Concerning Educational Robotics

Abstract: Current initiatives and laboratories concerning Educational Robotics (ER) are often not based on strong pedagogical backgrounds. Additionally, they are carried out by inadequately trained teachers, and are not evaluated properly in terms of effectiveness. Moreover, according to teachers, ER usability is often neglected. The main goal of the present article is to present a training course on ER (Edu.Ro.Co.), grounded in pedagogical insights, and to discuss the results of the course and teacher's opinion about E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
28
0
6

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(39 citation statements)
references
References 34 publications
(42 reference statements)
5
28
0
6
Order By: Relevance
“…This study was developed in the RobEd project framework during the Edu.Ro.Co. training course (Castro et al, ). The project was conducted in Italy and represents the first attempt to develop an ER curriculum able to explore the ER potential in different areas contemporaneously (cognitive, metacognitive, emotional and motivational, STEM areas).…”
Section: Aimmentioning
confidence: 99%
“…This study was developed in the RobEd project framework during the Edu.Ro.Co. training course (Castro et al, ). The project was conducted in Italy and represents the first attempt to develop an ER curriculum able to explore the ER potential in different areas contemporaneously (cognitive, metacognitive, emotional and motivational, STEM areas).…”
Section: Aimmentioning
confidence: 99%
“…On the other hand, one of the challenges faced when developing learning designs at schools is that teachers need to receive technical training on AI and robotics, as well as pedagogical training on how to integrate the use of AI and robotics on diverse subjects. Castro et al (2018) also found that training teachers on educational robotics is an important factor for the successful introduction of robotics in education. Nevertheless, the learning designs presented in this study could be used as examples by educators.…”
Section: Discussionmentioning
confidence: 94%
“…To be more precise, a lesson plan may be assigned as a follow-up activity after a training session (Nagchaudhuri and Mitra 2007) or the participants may be asked to create their own lesson plans and then discuss and/or present them in class (Kim et al ; Kim et al 2015). Participants may also be asked to create a pedagogical project to be applied in the classroom (Castro et al 2018), design their own robotics instructional materials for use in their future classes (Bers et al 2013), design worksheets that combine robotics and other subjects on the curriculum (Gilkes et al 2014) or develop multi-disciplinary didactic units and present them in class (Agatolio et al 2017). The training presented by Negrini (2019) moves a step further by suggesting that a database of robotics materials could be created and a community could be built to allow trainees to stay in contact after the training program has ended.…”
Section: Requirements For the Completion Of Er Trainingmentioning
confidence: 99%
“…Preschool teacher training is not as common as primary and secondary school teacher training. In the studies reviewed, only three training programs are held exclusively for preschool teachers (Bers et al 2002;Bers et al 2013; Caballero-González and Muñoz-Repiso 2017), while four training programs are held for preschool teachers as well as primary and secondary school teachers (Bers and Portsmore 2005;Castro et al 2018;Negrini 2019;Scaradozzi et al 2019). Even less common are training programs for special needs teaching staff since only two relevant studies were found.…”
Section: Trainer and Trainee Profilementioning
confidence: 99%
See 1 more Smart Citation